Kebijaksanaan Teknologi Tepat Guna untuk Petani Kecil - Fawzia Sulaiman (Forum penelitian Agro Ekonomi, 1996)
IndonesianThe majority of Indonesian farmers, especially farmers in Java, are small farmers. The number of farmers land holdings of less than 0.5 hectare totals 53.9 percent, those with 0.5 - 0.99 hectare are 22.1 percent, while those with 1 - 1.99 hectare are only 15.9 percent. However, these small farmers are main contributors to food production of the country. This implies that efforts to strengthen agribusiness system at local level will involve 90 percent of small farmers in Java with land holdings of less than 1.0 hectare, and 76 percent of total Indonesian farmers with the same level of land holdings. In this globalization era, there is a need of policy which is supportive to the appropriate technology for small farmers that enables them to manage their resources efficiently based on comparative advantage considerations. In this respect, agro ecosystem diversity and regional development stage in the country, availability and quality of natural and human resources, and local socio economic and cultural condition should be considered in technology generation and development. Several research results reported that the size of the land holding was one of the determinant factors in farmer's decision makin to adopt technology. The difference in the size of land holding, the farmer's productivity, and the availablity of supporting factors boosting agribusiness and agroindustry, indicates a different need of policy in technology development. Small farmers in Java need intensive land utilization technology, even non-land based techniques, and non-labor displacement technology. Thus, generating technology which is suitable for small farmers should be the main priority in agricultural research and development in Indonesia, at least in the coming few periods of the Five Year Development Plan (PELITA).